THE ROLE OF ORGANIZATIONAL COMMUNICATION IN BUILDING PUBLIC TRUST IN POLITICAL INSTITUTIONS: A COMPARATIVE LITERATURE REVIEW OF INDONESIA AND MALAYSIA - Aleta Fahraini Harahap; Dina A Chadijah Harahap; Farisa Rahman; John Hagai Sihombing; Feni Khairifa (OPINI: Journal of Communication and Social Science, 2026)
Public trust in political institutions has become a critical issue in emerging democracies, particularly in Southeast Asia. This study examines how organizational communication contributes to building public trust in political institutions through a comparative literature review of Indonesia and Malaysia. Using a systematic comparative review design, this research synthesizes 38 peer-reviewed studies published between 2014 and 2025. The analysis identifies thematic patterns related to communication structure, message consistency, digital engagement, and trust formation mechanisms. Findings indicate that Indonesia demonstrates relatively strong transparency and participatory openness but faces challenges in inter-agency coordination and message alignment. Conversely, Malaysia exhibits centralized communication coherence yet encounters limitations in dialogical engagement and public responsiveness. The study proposes an Alignment–Responsiveness Framework, suggesting that sustainable public trust emerges from the interaction between internal communication coherence and external responsiveness. This framework contributes to political organizational communication scholarship and offers strategic implications for designing trust-oriented public communication strategies in developing democracies